Electrical resistivity measurement of unsaturated concrete samples - Villagrán Zaccardi, Yury Andrés (2014)
Electrical conduction in concrete primarily occurs via the liquid in pores. Since concrete resistivity is sensitive to moisture content, resistivity can be used to infer other moisture-dependent concrete properties. However, quantitative assessment of the relationship between concrete resistivity and the pore liquid content can be a difficult task due to contact issues between electrodes and the surface of unsaturated concrete. Resistivity is usually measured using wet sponges to assess contact with a concrete surface. This is a very effective procedure for saturated concrete but implies minor alterations in the condition of unsaturated concrete. This paper deals with a contact method to measure the resistivity of unsaturated concrete samples. Resistivity measurements dispensing with wet contacts are performed on thin samples of conventional concrete. A dry contact is achieved by means of painted electrodes on the concrete surface. Dry and wet contact methods are compared when applied to saturated concrete, and resistivity values of unsaturated concrete are related to concrete moisture content and the relative humidity of the surrounding environment. As a result, resistivity is related to the volumetric fraction of conducting water in pores and its hygroscopic equilibrium with the surrounding environment.